Mondi in transito: Un’indagine di Ingo Schulze nella Russia post-sovietica (TEST Ticontre. Theory Text Translation, 2022)
This paper analyzes two short pieces from the debut collection of the German writer Ingo Schulze, 33 Augenblicke des Glücks (1993). The pieces highlight the attention of the author for the working class in the chaotic world of post-communist Russia, and are also indicative of the author’s reaction to the powerful penetration of Western capitalism in Eastern Europe after the fall of the Iron Curtain. This paper analyzes two short pieces from the debut collection of the German writer Ingo Schulze, 33 Augenblicke des Glücks (1993). The pieces highlight the attention of the author for the working class in the chaotic world of post-communist Russia, and are also indicative of the author’s reaction to the powerful penetration of Western capitalism in Eastern Europe after the fall of the Iron Curtain.